(untitled) (Communications in Computational Physics, 2011)
We propose a new multiscale method that couples molecular dynamics simulations (MD) at the atomic scale and finite element simulations (FE) at the continuum regime. By constructing the mass matrix and stiffness matrix dependent on coarsening of grids, we find a general form of the equations of motion for the atomic and continuum regions. In order to improve the simulation at finite temperatures, we propose a low-pass phonon filter near the interface between the atomic and continuum regions, which is transparent for low frequency phonons, but dampens the high frequency phonons.